Evaluation of learning environment variables in Turkey from the aspect of a learner's health and education - Tuncer, Murat (Sila Science, 2012)
In this study, the learning environment variables from the aspect of a learner's health and education are examined. For this purpose, measurements were taken from a random school in a province of Elazig and the results of these variables were compared for compatibility to literature on the subject. Humidity, temperature, light and noise measurements was performed by a DT 8820 Environment Meter, Oxygen, carbon dioxide, carbon monoxide was performed by a PN 66094 GMI and the magnetic field was measured with a SPECTRA AARONIA AG device. It was observed that based on the measurements of variables that the possibility of health problems arising in some of the learning environment could occur. The obtained measurements were to experience health problems due to variables in the learning environment in some classes.
Keywords: Learning environment; Learner's health; Air quality in the classroom; Physical variables